The Relationship Between Intensity of Social Media Use and Cyberbullying on Social Media - Husna, Jum’atul; Nito, Paul Joae Brett; Fetriyah, Umi Hanik; Ariani, Malisa (GLOBAL HEALTH SCIENCE GROUP, 2024)
The use of social media among teenagers is increasing, and the intensity of social media use among teenagers can result in cyberbullying behavior. One of the factors that influences cyberbullying behavior is the intensity of social media use and the increase in time spent doing online activities. The impact of cyberbullying behavior is a failure to develop social skills, such as empathy, negotiation and retaliation. Objective: To determine the relationship between the intensity of social media use and cyberbullying on social media at SMPN 3 Banjarmasin. Method: This research uses quantitative methods with a cross sectional research design. The population was 528 respondents and the sample size was 228 respondents using a stratified random sampling technique. Data were collected using a questionnaire on the intensity of social media use and cyberbullying behavior. The results of the validity of the media use intensity scale questionnaire with results of 0.500 – 0.654. Cyberbullying behavior scale questionnaire r calculated at 0.273 – 0.753. The results of the media use intensity scale questionnaire test were 0.625, and cyberbullying behavior scale questionnaire was 0.977. Which tested using the Kolmogorov Smirnov statistical test. Results: The results of the research are that the intensity of social media use among teenagers at SMPN 3 Banjarmasin is in the high significant category. Cyberbullying behavior among teenagers at SMPN 3 Banjarmasin is mostly in the high category. Conclusion : The results of the analysis show that there is a relationship between the intensity of social media use and cyberbullying behavior.